Nigeria Biannual Economic Update, April 2018 : Connecting to Compete - World Bank Group (World Bank, Washington, DC, 2018)
The Nigeria Biannual Economic Update is a product of the staff of the World Bank and has three broad aims. First, it reports on the key developments in the Nigerian Economy in the recent past Secondly, it summarizes the likely economic outcomes in the short-to-medium term, given the policy developments, and highlights key short-term risks and upside potentials. Finally, the Update provides a more in-depth examination of selected highly relevant economic issues. The Nigeria Biannual Economic Update is intended for a wide audience, including policy makers, business leaders, financial market participants, and the community of analysts and professionals engaged inNigeria’s economy.